2012
DOI: 10.1121/1.4740462
|View full text |Cite
|
Sign up to set email alerts
|

Increased intensity discrimination thresholds in tinnitus subjects with a normal audiogram

Abstract: Recent auditory brain stem response measurements in tinnitus subjects with normal audiograms indicate the presence of hidden hearing loss that manifests as reduced neural output from the cochlea at high sound intensities, and results from mice suggest a link to deafferentation of auditory nerve fibers. As deafferentation would lead to deficits in hearing performance, the present study investigates whether tinnitus patients with normal hearing thresholds show impairment in intensity discrimination compared to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 9 publications
1
19
1
1
Order By: Relevance
“…Previous observations that describe elevated intensity discrimination thresholds in tinnitus subjects with normal audiograms [75] may be re-examined in the context of a loss of signal-to-noise ratio in those frequency bands in which the BDNF-dependent driving force is lost. When the BDNF-dependent driving force is lost, the baseline levels required to allow the development of a normal adaptation of central brain responses after cochlear injury may be lost.…”
Section: Discussionmentioning
confidence: 99%
“…Previous observations that describe elevated intensity discrimination thresholds in tinnitus subjects with normal audiograms [75] may be re-examined in the context of a loss of signal-to-noise ratio in those frequency bands in which the BDNF-dependent driving force is lost. When the BDNF-dependent driving force is lost, the baseline levels required to allow the development of a normal adaptation of central brain responses after cochlear injury may be lost.…”
Section: Discussionmentioning
confidence: 99%
“…Hearing levels are displayed in Figure 2. However, inner ear damage is not necessarily obvious in the pure tone audiogram (Weisz et al, 2006; Schaette and McAlpine, 2011; Epp et al, 2012; Tan et al, 2013). Tinnitus patients with normal hearing thresholds have also more difficulties to understand speech in situations with background noise than persons without tinnitus (Hennig et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…The cause of the neuropathy in the tinnitus group is unclear, although it is tempting to speculate that it may have been noise exposure. Interestingly, it has been shown that people with tinnitus and normal hearing sensitivity have deficits in tone detection in noise (Weisz, Hartmann, Dohrmann, Schlee, & Norena, 2006) and intensity discrimination (Epp, Hots, Verhey, & Schaette, 2012). These might be further manifestations of cochlear neuropathy.…”
Section: Hidden Hearing Loss and Tinnitusmentioning
confidence: 99%